2021
DOI: 10.1016/j.ijdrr.2020.101987
|View full text |Cite
|
Sign up to set email alerts
|

Representation of disasters in school textbooks for children with intellectual disabilities in Iran: A qualitative content analysis

Abstract: School textbooks are one of the main sources for teaching and learning in an education system. This study aims to investigate the representation of disasters in school textbooks for the children with intellectual disabilities (ID) in the education system in Iran.This study uses a qualitative content analysis method. All school textbooks for students with ID in the education year 2019-2020 in Iran were collected. Among the whole 164 textbooks, 18 had content about hazards. Data were analyzed qualitatively by MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 62 publications
0
14
0
4
Order By: Relevance
“…Recently, the representation of disasters in textbooks for children with intellectual disabilities (ID) was investigated in a study in Iran. 25 Authors of that study indicated that 18 textbooks had content about natural hazards among 164 textbooks for children with ID in Iran. In addition, information about various natural hazards was presented in the textbooks for children with ID, including earthquakes, flood, extreme temperatures, droughts, storms, and epidemics.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the representation of disasters in textbooks for children with intellectual disabilities (ID) was investigated in a study in Iran. 25 Authors of that study indicated that 18 textbooks had content about natural hazards among 164 textbooks for children with ID in Iran. In addition, information about various natural hazards was presented in the textbooks for children with ID, including earthquakes, flood, extreme temperatures, droughts, storms, and epidemics.…”
Section: Literaturementioning
confidence: 99%
“…19 Textbooks play a significant role in education, and their role in addressing the disaster effects on children has been acknowledged. 20 Textbooks are important as most teachers rely on them for teaching. 21 Textbooks are the most vital educational sources and reflect the national culture and priorities in the country.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, children who live with disabilities may be affected more compared to than children without disabilities during disasters because societal and infrastructural factors limit their abilities 110 to move about. These may include movement disorders, medical needs, sensory disturbances, speech disorders, etc., each of which alone affects the appropriate response to disasters, and if several of these overlap, it increases vulnerabilities of children (Seddighi, Sajjadi, Yousefzadeh, et al, 2021b). Therefore, this group require prioritization special ,and more, training.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have previously been conducted on formal education to prepare children for disaster in schools in Iran. After examining students' textbooks and the curriculum of the Iranian educational system, suggest that in all educational levels, information about disasters was included in the curriculum (Seddighi, Sajjadi, Yousefzadeh, et al, 2021b;. In these studies, it was found that students become familiar with the nature of disasters with different origins, including geophysical, hydrological, climatological, meteorological, and biological disasters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation